STRATEGI PEMBELAJARAN MATEMATIKA BERDASARKAN KARAKTERISTIK ANAK USIA DINI - triana, Triana putri; idawati, Sulis ida; munawaroh, Hidayatu (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Children are very active learners and have their own world that is different from the adult world by building their own knowledge. The child's growth and development is greatly influenced by environmental conditions that create characteristics in children that must be understood by a teacher. Children's understanding and the development of the times also affect the mathematics learning system that becomes one of the competencies of a teacher to be able to help determine learning strategies and optimize them. The purpose of this study is to determine the strategies of mathematics learners based on the characteristics of children. The method used in this study is the study of literature. The results showed that the application of mathematics learning strategies in early childhood education starts from planning, namely understanding the characteristics of early childhood, deciding learning objectives, determining materials, and environmental settings. The implementation of education is supported by learning media and evaluation is carried out according to development indicators